Comparison of the biocompatibility of different root canal irrigants - Gomes-Filho, João Eduardo [UNESP]; Aurélio, Kamila Guilherme [UNESP]; Costa, Mariana Machado Teixeira De Moraes [UNESP]; Bernabé, Pedro Felício Estrada [UNESP] (FapUNIFESP (SciELO), 2008)
The purpose of this study was to compare the reaction of rat subcutaneous connective tissue to 0.9% sterile saline, 2.5% sodium hypochlorite (NaOCl), 5.25% NaOCl and 2% chlorhexidine gluconate solution or gel. Six circles were demarcated on the dorsal skin of 24 male Wistar rats, leaving 2 cm between each circle. Using a syringe, 0.1 mL of each root canal irrigant was injected subcutaneously into 5 circles. In the 6th circle, the needle of an empty syringe was introduced into the skin, but no irrigant was injected (control group). Evaluations were undertaken at 2 h, 48 h, 14 days and 30 days post-procedure. Tissue samples were excised, embedded in paraffin blocks and 3-μm-thick sections were obtained and stained with hematoxylin and eosin. The areas of inflammatory reaction were evaluated and analyzed statistically by ANOVA and Tukey's test. The control group showed few or no inflammatory reaction areas in the subcutaneous tissue. 0.9% saline solution, 2.0% chlorhexidine solution and 2.5% NaOCl showed a good biocompatibility, as very mild inflammatory reaction was detected at 14 days and tissue repair occurred at 30 days. 5.25% NaOCl was the most toxic irrigant, as the number of inflammatory cells remained elevated at 14 and 30 days. The group treated with 2.0% chlorhexidine gluconate gel presented a moderate inflammatory response at 14 days, which decreased at 30 days, being considered similar to that of the control group, 0.9% saline solution, 2.0% chlorhexidine solution and 2.5% NaOCl at this experimental period.
Keywords: Biocompatibility; Chlorhexidine; Root canal irrigants; Sodium hypochlorite